SH_OBERGERICHT 10/2008/1A vom 24. Juli 2009 - Sh Obergericht (2009)
Art. 29 Abs. 2 BV; Art. 254 Ziff. 1, Art. 256a Abs. 1 und Art. 256b ZGB; Art. 177 Abs. 1 und Art. 349 Abs. 2 ZPO | Anfechtung der Vaterschaftsvermutung; Beweisanspruch